Early Responses to Intravitreal Ranibizumab in Typical Neovascular Age-Related Macular Degeneration and Polypoidal Choroidal Vasculopathy - Matsumiya, Wataru (Hindawi Publishing Corporation, 2011)
Purpose. To evaluate the early response to intravitreal ranibizumab (IVR) in two different phenotypes of age-related macular degenerations (AMD): typical neovascular AMD (tAMD) and polypoidal choroidal vasculopathy (PCV). Methods. Sixty eyes from 60 patients (tAMD 28, PCV 32 eyes) were recruited. Three consecutive IVR treatments (0.5 mg) were performed every month. Change in the best-corrected visual acuity (BCVA) and central retinal thickness (CRT) was then compared between the tAMD and PCV groups. Results. The mean BCVA logMAR was significantly improved at month 1 and month 3 after the initial IVR in the tAMD group, but there was no change in the PCV group. Both phenotypes showed significant improvements in the CRT during the 3 months after the initial IVR. There were no significant differences in the improvements of the CRT in the tAMD versus the PCV group. In the stepwise analysis, a worse pretreatment BCVA and tAMD lesions were significantly beneficial for a greater improvement of BCVA at 3 months after the initial IVR. Conclusions. The phenotype of tAMD showed a significantly better early response to IVR than PCV in terms of BCVA improvement.